The Value of Subclinical Carotid Atherosclerosis for Primary Prevention of Cardiovascular Diseases. Review of the Main International Studies - E. K. Butina; E. V. Bochkareva (Рациональная фармакотерапия в кардиологии, 2016)
Measures for the prevention of cardiovascular diseases (CVD) are more effective if they are performed taking into account the risk factors of their development. Screening scales, which are helpful in determining the population risk, are used in primary prevention for cardiovascular (CV) risk stratification. The assessment of individual CV risk remains a problem. Biomarkers and instrumental investigations are used for its detailing. Carotid ultrasound is the main noninvasive method of vascular assessment. It allows assessing the intima-media thickness (IMT) and detecting the presence, location and morphology of atherosclerotic plaques (ASP), in other words, subclinical signs of atherosclerosis. Different views on the diagnosis of IMT and ASP in the carotid arteries and their value as predictors of CV and cerebrovascular diseases among individuals without CVD are presented in the article. Opinions about the benefits of IMT assessment for re-classification of patients with signs of subclinical atherosclerosis are also presented. The debate about the value of IMT in the CV risk stratification, and the feasibility of its assessment in clinical practice has not yet been completed. Assessment of IMT for CV risk stratification is most appropriate in patients with intermediate risk or with multiple risk factors of CVD. Consensus on primary CV prevention strategies in patients with intermediate risk of CVD is currently unavailable. Assessment of subclinical atherosclerosis by carotid ultrasound is important in such patients. The finding of increased carotid IMT should have an effect on the choice of hypolipidemic drug and intensity of treatment. However, the diagnosis of subclinical atherosclerosis is not built into the algorithm for determining the CV risk. This causes difficulties in choosing tactic of prophylactic intervention, especially for intermediate risk patients.